ANALISIS RASIO PROFITABILITAS PADA PERUSAHAAN DAGANG YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA TAHUN 2019-2023 - Kholig , Flirli; Agustin nengsih, Titin (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
The aim of this research is to find out how the Current Ratio, Debt to Equity Ratio, and Total Asset Turnover influence Return on Assets partially and simultaneously. This research uses a quantitative approach. The purposive sampling method, which means samples are selected based on certain standards, is used in the sample selection process. Financial data of trading companies listed on the Indonesian Sharia Stock Index is used in the financial reports studied for the 2019-2023 period. The type of data used is panel data. To analyze this data, panel data regression, classical assumption tests (such as normality, multicollinearity, heteroscedasticity and autocorrelation), hypothesis tests (such as t and F tests), and coefficient of determination are used. The research results show that Total Asset Turnover has a significant effect on Return On Assets, but the Current Ratio and Debt to Equity Ratio have no partial effect on Return On Assets